Educational strategies to improve health literacy for people with type 2 diabetes in low socio-economic communities: A realist review protocol - Namalambo Mwenda - Ng’uni; Martin Heine; Fastone Goma; Monika Martens; Miriam Mapulanga - Lisulo; Brown Kamanga; Inonge Milupi; Susan Hanekom (PLoS ONE, 2026)
Introduction Type 2 diabetes (T2D) has emerged among the top ten causes of disability and mortality worldwide. Health literacy is crucial for effective self-management to reduce the burden associated with T2D. Studies have reported the effectiveness of educational strategies for improving health literacy to promote good health and well-being. However, contextual factors influence the effectiveness of these strategies. Therefore, this paper intends to explain how and why context shapes the mechanisms through which educational strategies work to improve health literacy for adults with type 2 diabetes in low socioeconomic communities. Methods and analysis Theory-driven realist review methods will explain how and why contexts activate different mechanisms through which educational strategies work to produce intended or unintended outcomes in low socioeconomic communities. The following five steps of realist review, which are non-linear and iterative, will be undertaken: (i) Define the scope of the review and locate existing theories on educational strategies to improve health literacy, (ii) Develop the initial programme theories, (iii) Search for evidence, (iv) Select papers and appraise, and (v) Extract data and synthesis. The following databases will be searched, but not limited to, PubMed, Education Resource Information Centre (ERIC), and PsycINFO. Papers will be selected based on relevance, richness, and rigour. Data extraction will follow both inductive and deductive approaches. The Intervention-Context-Actor-Mechanism Outcome (ICAMO) configurations will be utilised to analyse and synthesise data using retroductive reasoning. Finally, the revised programme theories, which explain how the educational strategies are expected to work across different contexts in low socioeconomic communities, will be prepared and disseminated. Conclusion The findings may inform practice, influence policy, and contribute to the design of health literacy programmes in similar settings. The realist review is registered with the Open Science Framework: ( https://osf.io/9w867 )